Compiling Probabilistic Model Checking into Probabilistic Planning - Klauck, Michaela; Steinmetz, Marcel; Hoffmann, Jörg; Hermanns, Holger (Proceedings of the International Conference on Automated Planning and Scheduling, 2018)
It has previously been observed that the verification of safety properties in deterministic model-checking frameworks can be compiled into classical planning. A similar connection exists between goal probability analysis on either side, yet that connection has not been explored. We fill that gap with a translation from Jani, an input language for quantitative model checkers including the Modest toolset and PRISM, into PPDDL. Our experiments motivate further cross-fertilization between both research areas, specifically the exchange of algorithms. Our study also initiates the creation of new benchmarks for goal probability analysis.